Design, characterization and preliminary usability testing of a portable robot for unsupervised therapy of hand function - Ranzani, Raffaele; Albrecht, Martin; Haarman, Claudia J. W.; Koh, Emily; Devittori, Giada; Held, Jeremia P. O.; Tönis, Frederik J.; Gassert, Roger; Lambercy, Olivier (Frontiers in Mechanical Engineering, 2023)
Introduction: There is evidence that increasing therapy dose after stroke might promote recovery. Unfortunately, in clinical practice, therapy dose is limited by financial and organizational constraints. Simple robotic devices could be used without supervision in the clinic or at home to increase dose without requiring additional resources. For this purpose, we developed HandyBot, a portable three-degrees-of-freedom end-effector haptic device to perform sensorimotor task-oriented therapy of hand function (i.e., grasping, forearm pronosupination, wrist flexion-extension) in different environments. Methods: We present the mechatronic design of the device and its technical evaluation in terms of workspace, dynamics (i.e., max end-effector velocity, acceleration and force), sensing (i.e., position, velocity and force resolution) and haptic performance (i.e., transparency, maximum stable impedance range, rigid contact rendering accuracy). In addition, its feasibility and usability (in terms of System Usability Scale (SUS)) were assessed in a single-session experiment with four subjects with chronic stroke that tested the HandyBot therapy platform (i.e., haptic device with a graphical/physical user interface and a set of therapy exercises) while simulating unsupervised use (i.e., the subject used the device independently while a therapist was only observing the session). Results: HandyBot showed hardware and control performances comparable to other less portable therapy devices for hand function (e.g., 94% accuracy in stiffness rendering, low apparent mass of 0.2kg in transparency mode), making it a suitable platform for the implementation of sensorimotor therapy exercises. HandyBot showed good platform usability in terms of SUS (i.e., above 75 out of 100 for device and graphical user interfaces, above 65 out of 100 for the exercises) when tested in simulated unsupervised settings. These tests underlined minor design improvements that should be considered to allow using such a device in uncontrolled settings. Discussion: HandyBot is a novel robot for hand rehabilitation after stroke that revealed high-quality hardware and haptic performance. HandyBot was usable for stroke patients at first exposure for (simulated) unsupervised robot-assisted sensorimotor therapy of hand function. This therapy approach combined with this novel portable robotic device has the potential to help increase therapy dose and decrease therapy-associated costs (e.g., therapist time to therapy time ratio) in different environments.